Nurses' perceptions of continuing professional development: a qualitative study - Xiaoyan Yu; Yi Huang; Yu Liu (BMC, 2022)
Abstract Background Continuing professional development is regarded as one of the important approaches to maintaining skills and motivation for work. However, there is a lack of qualitative studies to explore Chinese nurses' continuing professional development. The study aims to explore Chinese nurses' perceptions of continuing professional development and challenges they face. Methods The study was conducted in a tertiary hospital located in the central region of China from July to August 2020. Purposive sampling was used to recruit 14 nurses and face to face semi-structured interviews were conducted from July to August 2020. Then the recorded data were analysed and collated according to the thematic analysis. This study followed the consolidated criteria for reporting qualitative research (COREQ). Results Four themes were extracted: improving specialty ability; different development phases; the importance of personal effort; the obstacle of work-family conflict. Conclusions This study contributed to our understandings of nurses' continuing professional development. Nurses held a positive attitude towards continuing professional development and they faced challenges in the meantime. Special attention and targeted supports should be provided to promote the continuing professional development of nursing staff.